452. Familial Cluster of COVID-19 Cases Associated with High Prevalence of Anosmia, Ageusia, and Gastrointestinal Symptoms - Ho, Bethany E (Open Forum Infect Dis, 2020)
BACKGROUND: Patients with COVID-19 most commonly report respiratory symptoms, with a minority reporting gastrointestinal (GI) symptoms in currently available reports. Additionally, little is known about the symptoms of anosmia/hyposmia, ageusia, and dysgeusia anecdotally seen in COVID-19 patients, which may be considered both GI and sensory/neurological manifestations of infection. METHODS: We interviewed 7 patients via oral inquiries and a questionnaire, collecting data on subject symptoms and their durations. Reverse transcriptase-polymerase chain reaction (RT-PCR) was used to confirm 2 of these cases. RESULTS: We report a familial cluster of 7 COVID-19 cases, 5 of whom reported sensory symptoms of anosmia/hyposmia (5/7), ageusia/hypogeusia (5/7), and/or dysgeusia (3/7). All 7 cases reported GI involvement with one or more symptom of: nausea (5/7), diarrhea (4/7), abdominal pain (3/7), anorexia (3/7), and emesis (2/7). Figure 1. Timeline of Symptoms and Exposure to Index Case in Familial COVID-19 Cluster [Image: see text] CONCLUSION: This frequency of GI symptoms is high relative to currently available epidemiological reports, which also infrequently report on sensory symptoms. The mechanistic underpinnings of GI and sensory symptoms in COVID-19 warrant close consideration and analysis, especially as it relates to reducing disease transmission. COVID-19 exhibits wide variation in duration, severity, and progression of symptoms, even within a familial cluster. DISCLOSURES: All Authors: No reported disclosures